Comparison of microleakage between direct placement technics and direct inlay technics. - (:unkn) unknown (My University, 1990)
Laboratory studies have indicated that improvements in the physical properties of composite restorations, especially for posterior teeth, may be obtained if these materials underwent heat treatment prior to insertion. The purpose of this study was to compare the microleakage in Class II restorations ending on cementum/dentine when these preparations were restored by a direct placement composite resin as opposed to a direct inlay composite resin. Thirty-six human posterior mandibular teeth were used in this study and randomly divided into three equal groups; Group I was prepared and restored with the composite Ful-fil in a direct placement technique. Groups II and III were prepared and restored using a direct composite resin inlay technique. The material used in Group II was Brillant D.I.; that of Group III, Ful-ful. All preparations terminated 1.0 mm apical to the CEJ. The composite resin patterns of Groups II and III were oven-tempered before cementing with D.I. Duo Cement. Specimens were thermocycled 125 times between 5-55 C. Microleakage was noted cervically on a scale of 0 to 5. The composite Ful-fil, used as a direct placement material, exhibited less leakage (P less than 0.05) than either the Brillant D.I. composite or Ful-fil composite when these materials were placed as direct composite inlays.